The effect of time slot parameters on slotted optical burst switched networks - Mohammad, Abu Bakar (2011)
In this study, the effects of time slot parameters on the performance of time domain switching optical burst switched networks (OBS) are studied. We investigate OBS networks where all core nodes are able to receive and send data. Network throughput is reduced when bursts are not able to secure necessary time slots for their transmission due to heavy contention at the core networks and lack of proper selection of time slot parameters. In this paper, we investigate the performance of slotted OBS when time slot parameters are varied. Time slot parameters investigated are: frame size, time slot size. Additionally, we analyse the effect of network size when time slot and other parameters are kept constant. Metrics used for evaluation are delay and throughput. Simulation results prove that given the same route, wavelength and time slot assignment algorithm, time slot parameters influence the overall network performance.